Anomie dan Penyimpangan Remaja: Adaptasi Ketegangan dalam Pencurian Buah Kelapa Sawit di Pedesaan - Gusniati; Rina Susanti (Jurnal Sosiologi Nusantara, 2026)
This research tries to analyze the motives behind young adult involvement in oil palm fruit bunch theft in Sikakak Village and to explain the phenomenon through the perspectives of social anomie and strain theory. This study used a case study design and a qualitative methodology. Purposively chosen informants were used to gather data through in-depth interviews, documentation, and observation. Results show that adolescent involvement in oil palm fruit bunch theft is driven by various motives: economic needs, entertainment needs, the desire for parental attention, and peer recognition. These findings suggest that theft functions as an adaptive response to the structural and relational pressures experienced by youth. From a strain theory perspective, the dominant pattern observed is innovation, particularly in economically motivated actions, while motives related to consumption and peer recognition tend to reflect rebellion. Meanwhile, from an anomie perspective, this phenomenon reflects the weakening of normative regulation due to economic inequality, family dysfunction, and shifting social values. This study concludes that adolescent involvement in oil palm theft reflects broader social dynamics.